UPAYA PERLINDUNGAN TERHADAP PEMEGANG HAK CIPTA REKAMAN LAGU PRODUKSI PT. RATU MUTIARA BUKITTINGGI - Sari, Lilian Perdana; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Lately, many still happened an act detrimental to the copyright belongs to arelated company, i.e. the Act of distributing unauthorized creation results that PT.Ratu Mutiara circulating in the form of tapes are not original. Formulation of theproblem in this research is whether the cause of the occurrence distribution ofunauthorized copyright recordings of song production PT. Ratu Mutiara and howefforts taken in addressing the unauthorized distribution. The purpose of thisstudy: first, to find out the cause of the occurrence distribution of unauthorizedrecordings of copyrighted songs. Second, to know the efforts taken by thecompany in addressing the unauthorized distribution.The type of research that the author use is a kind of sociological legalresearch. Location of research that became the object of the research is the PT.Ratu Mutiara. located at JL. Adinegoro No.11 Aur Kuning Atas of Bukittinggi,West Sumatra. While the population and sample is the entire parties relating toissues that are examined in this study. Data sources used are primary data andsecondary data. Data collection techniques in the study by observation,questionnaire, interview, and the study of librarianship.From the results of the research there were two basic problems that can beinferred. First, the cause of the still large number of unauthorized distributiontook place against the results of the related creation of copyright songs is causedby several factors, namely due to technological developments, price, copyrightprotection is still lacking was fulfilled, lack of awareness of the perpetrator andthe consumer. Second, the effort taken by PT. Ratu Mutiara in addressing theunauthorized distribution is in two ways. The first is a persuasive legal efforts,namely an approach undertaken by the company with the offender not todistribute unauthorized copyrighted property of the company. Second, with thelaw firm parties i.e. the actions reported to law enforcement. The author'ssuggestion, first, it is hoped to Department of law and human rights to giveguidance in an effort to increase understandings in the field of copyright. Theauthors also hope that law enforcement can be increasingly assertive and focus inaddressing problems of Copyright. Second, expected to law enforcers indetermining the rules of the country to consider that to minimize this cheatingshould sanctions not only charged to sellers, but in order to be charged to theconsumer as well.